Influence of HLA‐C environment on the spontaneous clearance of hepatitis C in European HIV–HCV co‐infected individuals. (2nd February 2021) - Legrand, N.; David, G.; Rodallec, A.; Gaultier, A.; Salmon, D.; Cesbron, A.; Wittkop, L.; Raffi, F.; Gendzekhadze, K.; Retière, C.; Allavena, C.; Gagne, K.
Summary: Natural killer (NK) cell functions are regulated by diverse inhibitory and activating receptors, including killer cell immunoglobulin‐like receptors (KIR), which interact with human leukocyte antigen (HLA) class I molecules. Some KIR/HLA genetic combinations were reported associated with spontaneous clearance (SC) of hepatitis C virus (HCV) but with discordant results, possibly reflecting KIR and/or HLA gene polymorphism according to populations. KIR/HLA genetic combinations associated with both an exhaustive NK and T cell repertoire were investigated in a cohort of HIV–HCV co‐infected individuals with either SC ( n = 68) or chronic infection (CI, n = 163) compared to uninfected blood donors [controls (Ctrl), n = 100]. Multivariate analysis showed that the HLA C2C2 environment was associated with SC only in European HIV–HCV co‐infected individuals [odds ratio (OR) = 4·30, 95% confidence interval = 1·57–12·25, P = 0·005]. KIR2D + NK cell repertoire and potential of degranulation of KIR2DL1/S1 + NK cells were similar in the SC European cohort compared to uninfected individuals. In contrast, decreased frequencies of KIR2DS1 + and KIR2DL2 + NK cells were detected in the CI group of Europeans compared to SC and a decreased frequency of KIR2DL1/S1 + NK cells compared to controls. Regarding T cells, higher frequencies of DNAX accessory molecule‐1 (DNAM‐1) + and CD57 + T cells were observed in SC in comparison to controls. Interestingly, SC subjects emphasized increased frequencies of KIR2DL2/L3/S2 + T cells compared to CI subjects. Our study underlines that the C2 environment may activate efficient KIR2DL1 + NK cells in a viral context and maintain a KIR2DL2/L3/S2 + mature T cell response in the absence of KIR2DL2 engagement with its cognate ligands in SC group of HCV–HIV co‐infected European patients. Abstract : Some KIR/HLA genetic markers and specific lymphocyte subsets are significantly associated with spontaneous clearance (SC) of HCV in European HIV–HCV co‐infected patients. In particular, European HIV–HCV co‐infected individuals with SC of HCV are characterized by an increased frequency of C2C2 environment compared to chronically infected individuals. This HLA‐C environment may favor an effective KIR2DL1+ NK cell response induced by a down‐regulation of HLA‐C molecules mediated by HIV on the cell surface on infected cells. An increased frequency of KIR2DL2/L3/S2+/DNAM‐1+/CD57+ T cells is also observed in European HIV–HCV co‐infected individuals with SC of HCV.